Benign Intracranial Hypertension Due to Hypoparathyroidism: A Case Report - Sforza, Giorgia; Deodati, Annalisa; Moavero, Romina; Papetti, Laura; Frattale, Ilaria; Vigevano, Federico; Cianfarani, Stefano; Valeriani, Massimiliano (Frontiers in Neurology, 2022)
Objective: To present the rare case of a young girl with idiopathic intracranial hypertension secondary to hypoparathyroidism. Backgrouds: Idiopathic intracranial hypertension is a neurological syndrome characterized by elevated intracranial pressure (>25 cmH2O) in the absence of intracerebral abnormalities or hydrocephalus. Pathophysiology of idiopathic intracranial hypertension is unknown and rare cases of idiopathic intracranial hypertension secondary to hypoparathyroidism have been described. It is supposed that hypocalcemia causes a decrease in the absorption of cerebrospinal fluid in the arachnoidal granulations. Methods: Workup of a girl with idiopathic intracranial hypertension and hypoparathyroidism, including physical examination, blood tests, diagnostic imaging, and lumbar puncture. Results: We present a 9-year-old female patient who was hospitalized for headache associated with nausea and vomiting for 3 weeks. She underwent ophthalmologic examination revealing papilledema. Lumbar puncture revealed an opening pressure of 65 cm H2O; cerebrospinal fluid analysis and brain computed tomography scan were normal. The patient started taking acetazolamide. Blood tests revealed hypocalcemia associated with high phosphorus level and undetectable PTH hormone, thus leading us to suspect hypoparathyroidism. She had never had cramps, paraesthesias or tetany. Chvostek's and Trousseau's signs were positive. At neck ultrasonography parathyroids were not visible. Oral supplementation with calcitriol and calcium was started. Headache, nausea and vomiting immediately disappeared after lumbar puncture, while papilledema improved gradually. Conclusions: Few anecdotal cases of idiopathic intracranial hypertension secondary to hypoparathyroidism have been described. However, our case report is of particular interest since the child did not present with the typical neurological hypoparathyroidism symptoms. Therefore, we recommend that hypoparathyroidism should be included in the diagnostic investigations in children with clinical findings of idiopathic intracranial hypertension because clinical manifestations of hypoparathyroidism are variable and may involve almost all organ systems.